2010
DOI: 10.1038/sc.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skin perfusion response with alternating and constant pressures in people with spinal cord injury

Abstract: Study design: Two-way factorial mixed design, the between-subjects factor as the spinal cord injury (SCI) status (SCI and non-SCI) and the within-subjects factor as the pressure pattern (alternating and constant pressures). Objectives: To compare the effects of alternating and constant pressures on weight-bearing tissue perfusion in people with SCI, with application for improving alternating pressure support surface usage. Setting: University research laboratory. Subjects: A total of 28 participants were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 25 publications
1
56
0
Order By: Relevance
“…Empirically, there is evidence linking increased mechanical loading with increased pressure ulcer incidence in elderly wheelchair users [12]. Clinically, best-practice guidelines recommend routinely performing pressure-relieving maneuvers to further manage pressure ulcer risk [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…Empirically, there is evidence linking increased mechanical loading with increased pressure ulcer incidence in elderly wheelchair users [12]. Clinically, best-practice guidelines recommend routinely performing pressure-relieving maneuvers to further manage pressure ulcer risk [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…Hagisawa et al showed that people with SCI take longer to reach peak hyperemia after removal of loading pressure [29]. Jan et al showed that pressure loadings (alternating and constant pressures) induce different skin blood flow response between people with SCI and nondisabled controls [28]. Nicotra et al observed a lower ratio of the first peak to baseline blood flow at the level below the lesion in people with complete high-level SCI (cervical 6 to thoracic 5) as compared with people with low-level SCI (thoracic 6 to 11) [26].…”
Section: Discussionmentioning
confidence: 99%
“…The finding may contribute to our long-term goal of using BFO patterns for the early detection of pressure ulcers in people with SCI [7,9,18]. Vasodilatory function could be used to quantify risk for pressure ulcers in people with SCI [25][26][27]; people with SCI who fail to increase skin blood in response to a causative factor of pressure ulcers (pressure, shear, or heating) are susceptible to pressure ulcers [27][28]. Schubert and Fagrell demonstrated that people with SCI have impaired vasodilatory response to either local heating or local pressure [27].…”
Section: Discussionmentioning
confidence: 99%
“…The study of skin microcirculation has been shown to be useful to assess risk for pressure ulcers [14]. Recently, skin blood flow response to local heat has been used to assess microvascular regulation using wavelet analysis [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%